The Relationship Between Family Support and the Participation of Mothers of Children Under Five in Posyandu Activities at Lembang Saiyo Posyandu, Balimbiang Hamlet, Tanah Datar Regency - Difa Salsabila Putri; Mhd Natsir (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2026)
This research was driven by the low involvement of mothers with toddlers in posyandu activities at Posyandu Lembang Saiyo, Jorong Balimbiang, Tanah Datar Regency, which is suspected to stem from insufficient family support. The research sought to describe the state of family support, the extent of mothers' participation, and the connection between these two elements. It adopted a quantitative method with a correlational design. The research population consisted of 50 mothers with toddlers, from which 38 individuals were selected as the sample via purposive sampling. Data were gathered using questionnaires that had undergone prior validity and reliability testing. Data analysis incorporated descriptive statistics through percentages and inferential analysis via Pearson product moment correlation. Findings indicated that family support fell into the low category, while mothers' participation with toddlers was also low, particularly in terms of activeness and discipline. Hypothesis testing confirmed a significant and robust link between family support and mothers' participation, with a correlation coefficient of 0.787. In conclusion, greater family support correlates with elevated participation by mothers in posyandu activities. Thus, bolstering family support is vital for enhancing mothers' engagement in community health initiatives.Keywords: family support, participation, mothers with toddlers, posyandu